2021
DOI: 10.1088/1742-6596/1918/4/042044
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of factors influencing Gross Regional Domestic Product (GRDP) in East Java: a spatial durbin error model analysis

Abstract: Regression analysis is not always a suitable solution if the analyzed data contains spatial effects. In overcoming the spatial effect on the data, a statistical method that can overcome it is needed. Spatial regression is a method used for data that has a location effect. One of the spatial regression model that can be used is the spatial Durbin error model. Spatial Durbin error model can overcome the spatial autocorrelation relationship in the independent variables and overcome the spatial error between regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…GRDP of the Agricultural Sector (Sulistyowati et al, 2020) partially has a positive and significant effect on the Human Development Index (HDI) in West Sulawesi Province. GRDP as an indicator of economic growth (Kholifia et al, 2021;Syaraswati et al, 2017) can increase people's welfare as indicated by the Human Development Index (HDI). It is because economic development guarantees increased productivity (Beck et al, 2018;Borcan et al, 2018;Teignier, 2018) and increased income through job creation.…”
Section: Introductionmentioning
confidence: 99%
“…GRDP of the Agricultural Sector (Sulistyowati et al, 2020) partially has a positive and significant effect on the Human Development Index (HDI) in West Sulawesi Province. GRDP as an indicator of economic growth (Kholifia et al, 2021;Syaraswati et al, 2017) can increase people's welfare as indicated by the Human Development Index (HDI). It is because economic development guarantees increased productivity (Beck et al, 2018;Borcan et al, 2018;Teignier, 2018) and increased income through job creation.…”
Section: Introductionmentioning
confidence: 99%
“…GRDP calculation is a very important part in macroeconomics, especially regarding the economic analysis of a region [2] [3]. GRDP can measure the rate of economic growth [4]. Based on data from the Central Statistics Agency (BPS), Indonesia's economic growth in the second quarter of 2022 reached 5.44% (y-o-y).…”
Section: Introductionmentioning
confidence: 99%